The Cultural Factors of Defence Reforms: The Case of Taiwan - Marcel Mangold (International Journal of Asia Pacific Studies, 2026)
Contributing to the debate on Taiwan’s defence build-up and scholarship on military change, this study explores cultural factors in the military and across society that shape defence reforms in Taiwan in the 2020s. Drawing on data from official documents, secondary literature, and twelve elite interviews with actors in the Taiwanese security sector, this study explores reforms to the force structure since 2022, the shift to an asymmetric warfare strategy, and efforts to build a whole-of-society defence. The findings show that the force structure and mobilisation reforms are limited by a military culture that undervalues conscripts and reserves, valuing stable routines. The reforms are also limited by the structure of civil-military relations. The reforms towards an asymmetric warfare strategy have been limited by resistance to unconventional methods of warfare, the Ministry of National Defence’s wish to safeguard its monopoly over the armed forces, and by the existing command culture and procurement priorities linked to the different services. Lastly, reforms towards whole-of-society defence take place in the context of a historical devaluation of civil defence, institutional resistance from the Ministry of National Defence to share defence with civilian agencies, and military and political suspicion of trained civilians. However, the findings showed that changes in threat perceptions and practical training experiences have mobilised civilians and increased acceptance of civil preparedness. By indicating how cultural factors intersect and make change more or less likely, the findings have implications for scholarship on cultural factors behind military change, for debates on Taiwan’s defence build-up, and for Taiwan’s defence.